EFEKTIFITAS PEMANFAATAN KULKUL DESA DALAM KEGIATAN KEAGAMAAN DI DESA PENGOTAN - AYU WADANTI (Jurnal Anala, 2012)
Pengotan village is one of the villages that still preserves the value of traditional mountain village. Pengotan village as Bali Aga one is divided into 8 banjars dinas and a adat village. In terms of social life, the village of Pengotan still maintains a traditional communication systems in religious activities at the village, as the village Kulkul uses for the medium of communication on the mass wedding implementation. The study was conducted in order to determine the traditional communication systems in terms of Kulkul village utilization, especially in religious activities at the Pengotan village, and to try linking the traditional communication systems to rural tourism development efforts, so the future can work better and be an awake sustainability. The fieldwork uses descriptive qualitative research methods. It is conducted to describe the state or condition of the traditional communication systems at Pengotan village. As for the results obtained from this study, the Kulkul village has an important role on the mass wedding implementation at the Pengotan village. It’s considered valid until the brides become husband and wife. Kulkul existence as a traditional communication village media can not be separated from Prajuru Desa’s and Kesinoman’s role. When it’s associated with the development of rural tourism Pengotan, the traditional communication systems are implemented in a mass wedding and those can be used as a tourist attraction to come and get knowing more the Balinese diverse culture Keywords: Pengotan Village - Traditional Communication Systems - Kulkul Village - Rural Tourism